Correction: Seed dressing with mefenpyr-diethyl as a safener for mesosulfuron-methyl application in wheat: The evaluation and mechanisms. - PLOS One Staff (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0256884.].